Sphingosine-1-Phosphate Receptor-2 Antagonists: Therapeutic Potential and Potential Risks - Blankenbach, Kira V.; Schwalm, Stephanie; Pfeilschifter, Josef; Meyer zu Heringdorf, Dagmar (Frontiers in Pharmacology, 2016)
The sphingosine-1-phosphate (S1P) signalling system with its specific G-protein-coupled S1P receptors, the enzymes of S1P metabolism and the S1P transporters, offers a multitude of promising targets for drug development. Until today, drug development in this area has nearly exclusively focused on (functional) antagonists at the S1P1 receptor, which cause a unique phenotype of immunomodulation. Accordingly, the first-in class S1P1 receptor modulator, fingolimod, has been approved for the treatment of relapsing-remitting multiple sclerosis, and novel S1P1 receptor (functional) antagonists are being developed for autoimmune and inflammatory diseases such as psoriasis, inflammatory bowel disease, lupus erythematodes, or polymyositis. Besides the S1P1 receptor, also S1P2 and S1P3 are widely expressed and regulate many diverse functions throughout the body. The S1P2 receptor, in particular, often exerts cellular functions which are opposed to the functions of the S1P1 receptor. As a consequence, antagonists at the S1P2 receptor have the potential to be useful in a contrasting context and different areas of indication compared to S1P1 antagonists. The present review will focus on the therapeutic potential of S1P2 receptor antagonists and discuss their opportunities as well as their potential risks. Open questions and areas which require further investigations will be emphasized in particular.